Low-dose gonadotropin induction of ovulation in anovulatory women: still needed in the age of IVF. Issue 1 (July 2018) - White, Davinia M; Hardy, Kate; Lovelock, Suzannah; Franks, Stephen
Abstract : Low-dose, step-up gonadotropin is the treatment of choice for women with polycystic ovary syndrome (PCOS) who have not conceived after anti-oestrogen treatment and as an effective alternative to pulsatile GnRH in women with hypogonadotropic hypogonadism (HH). There has been, however, no large-scale, comparative study between the two groups using low-dose gonadotropins. Here, we performed a retrospective, comparative analysis, in a single clinic database, of efficacy and safety of induction of ovulation using low-dose gonadotropins in 364 women with PCOS and 80 women with HH. The rate of ovulation was high in both PCOS (83%) and HH (84%) but mono-follicular, ovulatory cycles were more prevalent in PCOS than in HH (77% vs 53%, P  < 0.0001) and the proportion of cycles that were abandoned was higher in HH than in PCOS (25% vs 15%, P  < 0.0001). The median threshold dose of gonadotropin required to induce ovulation was 75 IU/day in PCOS and 113 IU/day in HH ( P  < 0.001) and the range of doses was greater in HH women. Forty-nine percent of women with PCOS and 65% of those with HH conceived (more than 90% within 6 cycles of treatment) and had at least one pregnancy. Multiple pregnancies (all twins) occurred in only 4% of women with PCOS and 5% of those with HH. These findings emphasise the efficacy and safety of low-dose gonadotropin treatment for both clomiphene-resistant women with PCOS and those with HH. These results highlight the importance of choosing the more physiological approach of gonadotropin induction of ovulation in both groups as the most appropriate treatment, in preference to IVF.